Early onset ACS: An age based clinico-epidemiologic and angiographic comparison. (December 2018) - Chhabra, Shibba Takkar; Kaur, Tripat; Masson, Sarbjit; Soni, Ravinder K.; Bansal, Namita; Takkar, Brijesh; Tandon, Rohit; Goyal, Abhishek; Singh, Bhupinder; Aslam, Naved; Mohan, Bishav; Wander, Gurpreet Singh
Abstract: Background and aims: Acute coronary syndrome (ACS) in the very young is a rare entity, with limited data. We aimed to study patterns and profile of ACS in patients aged 20–30 years in comparison with those above 30 years. Methods: In this retrospective record-based study, the demographic and clinical profile of all patients with ACS in the last 12 years (n = 35259) was analysed: group I (20–30 years) and group II (above 30 years). Patients in group II were selected by systematic sampling. Age, gender, domicile, body mass index (BMI), serum cholesterol, smoking, alcohol use, drug abuse, diabetes, hypertension, family history, type of ACS, angiographic findings and management strategies were recorded. Chi-square test and Fischer's exact test were used for data analysis. Results: Of 35, 259 patients, 0.32% (n = 114) were from the younger age group, with a rising trend of prevalence over 12 years. Obesity, overweight, urban living, smoking, alcohol and drug abuse were significantly higher in group I ( p <  0.05). Diabetes mellitus and hypertension were more prevalent in group II ( p =  0.001). STEMI in group I (76.3%) and NSTEMI in group II (47.1%) were the common modes of presentation ( p =  0.001). 42.1% of group I patients had recanalized coronaries with conservative management in comparison to 3% in group II ( p =  0.001). Conclusions: There is a rising trend in prevalence of ACS in very young patients. Overweight, obesity, urbanization and drug abuse are potential risk factors. The younger subset of ACS patients is different from the older population due to their thrombotic milieu, which could be more amenable to intensive pharmacologic management. Graphical abstract: Image 1 Highlights: Largest study of ACS in patients younger than 30 years. Rising trend in prevalence of ACS in very young patients in a 12-year study period. Overweight, obesity, urbanization and drug abuse are potential risk factors. Thrombotic milieu in the very young versus fibrotic calcific atherosclerotic milieu in the older subset. Higher recanalisation rates in the very young with intensive pharmacological management.